Objective validity of an implant-retained overdenture with a ball attachment system after marginal mandibulectomy. Issue 2 (February 2016) - Murase, Ryuichi; Ishikawa, Akiko; Sumida, Tomoki; Shinohara, Kozue; Nakashiro, Koh-ichi; Hamakawa, Hiroyuki
Abstract: Implant-retained overdentures are known to improve oral function, but the clinical impact on patients who have had mandibular resections is still debatable. We have treated 16 patients who had such resections for oral cancer and consequent loss of the alveolar ridge, with overdentures supported by osseointegrated implants and ball attachments. To quantify their functional improvement, we evaluated their maximum bite force and masticatory performance. Their function improved significantly, (from 77.5 N - 365 N, 371% increase in maximum bite force, p<0.001) and masticatory performance increased (from 2.5 - 7.7, 208%, p<0.0001) after the overdentures had been inserted. While individual changes in maximum bite force showed no significant correlation, those in masticatory performance correlated significantly, which suggests that the subjects with poor masticatory function are likely to benefit from retention of an implant. These results indicate that implant-retained overdentures are an effective way to rehabilitate patients after marginal mandibular resection.